2013
DOI: 10.1186/1471-2164-14-203
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and evolution of ACGT repeat cis-element landscape across four plant genomes

Abstract: BackgroundTranscription factor binding is regulated by several interactions, primarily involving cis-element binding. These binding sites maintain specificity by means of their sequence, and other additional factors such as inter-motif distance and spacer specificity. The ACGT core sequence has been established as a functionally important cis-element which frequently regulates gene expression in synergy with other cis-elements. In this study, we used two monocotyledonous – Oryza sativa and Sorghum bicolor, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…It is reported that these G-boxes are differentially regulated by the distance between two copies of the motif (Mehrotra and Mehrotra, 2010). Moreover, the G-box copy number in a promoter, and the distance from the transcriptional start site, also result in drastically altered gene expression, causing changes in the pattern of expression and even in resistance (Mehrotra et al, 2005(Mehrotra et al, , 2013. Thus, the degree of conservation of different regulatory elements may decrease depending on the motif in monocots and dicots.…”
Section: Dna Sequence Variation In Mir168 Promoter Regionsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that these G-boxes are differentially regulated by the distance between two copies of the motif (Mehrotra and Mehrotra, 2010). Moreover, the G-box copy number in a promoter, and the distance from the transcriptional start site, also result in drastically altered gene expression, causing changes in the pattern of expression and even in resistance (Mehrotra et al, 2005(Mehrotra et al, , 2013. Thus, the degree of conservation of different regulatory elements may decrease depending on the motif in monocots and dicots.…”
Section: Dna Sequence Variation In Mir168 Promoter Regionsmentioning
confidence: 99%
“…However, the most interesting results relate to the copy number of the G-box (CACGTG) of MIR168 promoters from different species were different. G-box (CACGTG) is the most prevalent G-box in all ACGT classes ACGT classes (Figure 1 and S1 Figure) (Mehrotra et al, 2013). The MIR168 promoter of A. thaliana contains three G-box motifs (CACGTG) (Gazzani et al, 2009).…”
Section: Dna Sequence Variation In Mir168 Promoter Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our reporter assays demonstrate that even subtle sequence variation within the OSRE1 consensus itself alters enhancer activity, and such alterations could be important for tuning the degree of salinity induction of different genes. Another evolutionary mechanism for tuning environmental responsiveness of gene expression pertains to alteration of copy number for a particular CRE (84,85). Thus, the difference in the number of OSRE1 motifs in the MIPS of O. mossambicus and O. niloticus (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using gene expression databases we also observed trends suggesting that co occuring ACGT elements are responsible for gene regulation in response to exogenous stress. Conservation in patterns of ACGT (N) ACGT among orthologous genes also indicated the possibility that emergence of functional significance across species was a result of parallel evolution of these cis elements [1].…”
Section: Short Commentarymentioning
confidence: 99%